Groundwater depletion in the Jordan highlands: can pricing policies regulate irrigation water use? - Venot, Jean-Philippe; Molle, Francois (2008)
Jordan is one of the countries with the scarcest water resources in the world. The aquifers of the Lower Jordan River Basin, a region of prime importance for the country, are exploited well beyond their sustainable rate. In 1997, Jordan's officials designed a new water strategy, with emphasis on demand-management instruments. Water pricing policies, and notably the bylaw no. 85 of 2002, were deemed to assist in controlling agricultural groundwater abstraction with the ambitious task of taking the abstraction rate close to the annual recharge. While much hope has been placed in such strategies, this paper argues that substantial increases in volumetric charges would not result in major water savings but would further decrease the income from low-value or extensive crops. A shift towards highvalue crops would raise water productivity but would also entail a transfer of wealth to the government and to wealthier entrepreneurs. It is therefore essential that negative incentives be accompanied by positive measures offering attractive alternatives (market opportunities, subsidies for modernization, technical advice, etc.) and exit options with compensation. Prices are unlikely to enable regulation of groundwater abstraction and significant reduction will only be achieved through policies that reduce the number of wells in use, such as buying out of wells.